TINGKAT INFESTASI CACING HATI PADA SAPI BALI DI KECAMATAN SUKOHARJO KABUPATEN PRINGSEWU PROVINSI LAMPUNG - Dea Fitri Aryandrie; Purnama Edy Santosa; Sri Suharyati (JURNAL ILMIAH PETERNAKAN TERPADU, 2015)
Research to find out liver fluke infestation level of Bali cattle in Sukoharjo sub-district, Pringsewu Regency, Lampung Province was implemented in December 2014 until January 2015.  The method used is the method of survei and sampling of Bali cattle were selected by proportional random sampling.  Sampling on cattle according to the population in each village and were collected proportionally by every 100 individuals represented by one Bali cattle farmer.  To correct for multiple stage sampling either on a sample of cattle and farmers, so the number of cattle and farmers multiplied by four, in order to obtained 131 faecal samples Bali cattle.  Data were analyzed descriptively.  Stool examination conducted by using Sedimentation Test.  The results showed liver fluke infestation level in Sukoharjo sub-district is 27,62% that there were 35 positive samples infested from 131 faecal samples were examined.   (Keywors :infestation level, liver fluke, Bali cattle).